Friction between ski and snow - Nachbauer, W.; Kaps, P.; Hasler, M.; Mössner, M (The engineering approach to winter sports, 2016)
Besides practical ski development, a lot of knowledge about the friction processes was gained. The initial considerations of friction on snow regarded dry friction. Soon the reason for the low friction on snow and ice was presumed to lie in a thin water film. This water film was first supposed to be generated by pressure melting. Ice melts at lower temperature when additional pressure is applied. Energy considerations led to another theory. At snow temperatures relevant for skiing, the heat generated by friction is sufficient to melt snow. This process causes lubricated friction, which is now considered as the dominant friction regime of skis on snow. In the last decade, an additional theory came up. Quasi-liquid films were observed due to premelting even below the melting point of crystals which supposedly have an effect on snow friction.